Cerebral Vessels: An Overview of Anatomy, Physiology, and Role in the Drainage of Fluids and Solutes - Agarwal, Nivedita; Carare, Roxana Octavia (Frontiers in Neurology, 2021)
The cerebral vasculature is made up highly specialized structures that assure constant brain perfusion necessary to meet the very high demand for oxygen and glucose by neurons and glial cells. A dense, redundant network of arteries is spread over the entire pial surface from which penetrating arteries dive into the cortex to reach the neuro vascular units. Besides providing blood to the brain parenchyma, cerebral arteries are key in the drainage of interstitial fluid (ISF) and solutes such as amyloid-beta. This occurs along the basement membranes that surround vascular smooth muscle cells, towards leptomeningeal arteries and deep cervical lymph nodes. The dense microvasculature is made up of fine capillaries. Capillary walls contain pericytes that have contractile properties and are lined by a highly specialized blood brain barrier that regulate the entry of solutes and ions and maintain the integrity of the composition of ISF. They are also important for the production of ISF. Capillaries drain into venules that course centrifugally towards the cortex to reach cortical veins and empty into dural venous sinuses. The walls of the venous sinuses are also home to meningeal lymphatic vessels that support drainage of cerebrospinal fluid (CSF), although such pathways are still poorly understood. Damage to macro and microvasculature will compromise cerebral perfusion, hamper the highly synchronized movement of neurofluids, affect drainage of waste products leading to neuronal and glial degeneration. This review will present vascular anatomy, their role in fluid dynamics and a summary on how their dysfunction can lead to neurodegeneration.